The Food Warden: An Exploration of Issues in Distributing Responsibilities for Safe-by-Design Synthetic Biology Applications. - Robaey, Zoë; Spruit, Shannon L.; van de Poel, Ibo (Science & Engineering Ethics, 2018)
The Safe-by-Design approach in synthetic biology holds the promise of designing the building blocks of life in an organism guided by the value of safety. This paves a new way for using biotechnologies safely. However, the Safe-by-Design approach moves the bulk of the responsibility for safety to the actors in the research and development phase. Also, it assumes that safety can be defined and understood by all stakeholders in the same way. These assumptions are problematic and might actually undermine safety. This research explores these assumptions through the use of a Group Decision Room. In this set up, anonymous and non-anonymous deliberation methods are used for different stakeholders to exchange views. During the session, a potential synthetic biology application is used as a case for investigation: the Food Warden, a biosensor contained in meat packaging for indicating the freshness of meat. Participants discuss what potential issues might arise, how responsibilities should be distributed in a forward-looking way, who is to blame if something would go wrong. They are also asked what safety and responsibility mean at different phases, and for different stakeholders. The results of the session are not generalizable, but provide valuable insights. Issues of safety cannot all be taken care of in the R&D phase. Also, when things go wrong, there are proximal and distal causes to consider. In addition, capacities of actors play an important role in defining their responsibilities. Last but not least, this research provides a new perspective on the role of instruction manuals in achieving safety.